EFFECTS OF RED DRAGON FRUIT PEEL EXTRACT ADMINISTRATION ON NEUTROPHIL COUNTS FOLLOWING PERIAPICAL RADIOGRAPHY EXPOSURE - Maydina Izzatul Yazidah; Didit Aspriyanto; Renie Kumala Dewi (FKG Unlam, 2021)
Background: Radiation exposure from periapical imaging can cause cell damage in various tissues due to the formation of free radicals. Cell damage in the tissue can be observed from the number of neutrophils which are immune cells. Free radicals can be suppressed by administering exogenous antioxidants. One source of natural antioxidants is red dragon fruit, especially on its peel. Objective: To analyze the effect of periapical imaging x-ray radiation exposure after the administration of red dragon fruit peel extract on absolute neutrophil counts in mice. Method: This research was a true experimental study with a post-test only and control group design using 24 mice that were divided into 6 groups. The control group was not given any treatment while P1 to P5 group were given red dragon fruit peel extract at a dose of 100 mg/kg BW and exposed to radiation with different exposures. P1 group was exposed 1 time (0.63 mGy), P2 group was exposed 4 times (1.66 mGy), P3 group was exposed 8 times (4.37 mGy), P4 group was exposed 12 times (8.19 mGy), and group P5 was given no exposure. Results: There were changes in the number of neutrophils in all groups. The LSD Posthoc test results showed a significant difference between the control group (12.470 / mm3) and the P5 group (12.470 / mm3) compared to P3 group with 8 times exposure (40.348 / mm3). Conclusion: There is an effect of periapical radiographic x-ray radiation exposure by red dragon fruit peel extract on the absolute neutrophil count in mice. Keywords: Antioxidants, Neutrophils, Periapical Radiography, Radiation, Red Dragon Fruit Peel.